Vestibular organ in patients with systemic lupus erythematosus - Maciaszczyk, Katarzyna; Józefowicz-Korczyńska, Magdalena; Waszczykowska, Elżbieta; Pajor, Anna; Erkiert-Polguj, Anna; Durko, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Vertigo and balance disorders as a result of immune-mediated inner ear damage may occur in systemic lupus erythematosus (SLE). Aim: To evaluate vestibular organ impairment in SLE patients in relation to duration of the disease, type and severity dependent on renal and central nervous system (CNS) involvement and presence of certain types of autoantibodies. Material and methods : The study group was 34 patients with SLE (mean age 47.6 ±11.4 years) complying with international diagnostic SLE criteria of the American Rheumatism Association. The anamnesis was in the form of a questionnaire. The control group consisted of 30 healthy persons (mean 47.8 ±9.8 years). In all persons laryngological examination and static and dynamic balance tests were performed. The vestibular organ was evaluated using electronystagmography (ENG). We recorded spontaneous nystagmus with eyes open and closed then optokinetic, smooth pursuit and positional tests. Kinetic torsion swing test and caloric test by Hallpike method were also carried out. Results: In laryngological examination 73.5% of SLE patients reported vertigo, 61.8% balance disturbances, 41.2% tinnitus, 25.7% hyperacusis, 29.4% hearing loss, 26.5% hyperacusis. In 24 (70.6%) SLE patients vestibular system impairment in ENG recordings were found. Central signs were observed in 10 (29.4%), mixed in 8 (23.5%) and peripheral in 6 patients (17.6%). Abnormal ENG outcomes in SLE patients were significantly more often recorded than in the control group. No statistical differences were found between the abnormal results of ENG tests and antibody presence or CNS involvement but weak significance concerning only patients with renal involvement. Conclusions: Vertigo and balance disturbances seem to be important clinical symptoms of SLE. In over half of SLE patients vestibular organ impairment was observed.